External field enhanced NiCo2S4-coated NiFeLDH / N-rGO heterostructure composite material and application thereof
By using the field-enhanced NiCo2S4@NiFe LDH/N-rGO heterostructure composite, the problem of ORR and OER kinetic obstacles in zinc-air batteries is solved, and better electrocatalytic performance and application performance of zinc-air batteries are achieved.
Patent Information
- Application Number
- CN202411617516.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The kinetics of oxygen reduction reaction (ORR) and redox reaction (OER) in existing zinc-air batteries (ZABs) hinder their practical application, especially in flexible equipment and extreme temperature conditions.
The field-enhanced NiCo2S4@NiFe LDH/N-rGO heterostructure composite was used as the electrocatalytic material. NiCo2S4@NiFe LDH was synthesized by hydrothermal method and combined with graphene to form NiCo2S4@NiFe LDH/N-rGO heterostructure composite material to improve its electrocatalytic performance.
The ORR and OER electrochemical performance of NiCo2S4@NiFe LDH/N-rGO is significantly improved, and its battery performance in ZABs is enhanced, especially under photothermal conditions, and the energy conversion and storage efficiency of zinc-air batteries are improved.
Smart Images

Figure CN119786550A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical materials, and in particular to an external field enhanced NiCo2S4@NiFe LDH / N-rGO heterostructure composite material and applications thereof. Background Art
[0002] Pursuing green renewable energy and adopting innovative energy storage technologies are of vital strategic significance. Currently, lithium-ion batteries dominate the energy storage market, especially in consumer applications. However, existing lithium-ion battery technology faces the problem of insufficient energy density (50-260Wh kg -1 ), high operating costs, and potential safety issues have restricted its further development and utilization. Therefore, it is imperative to develop the next generation of energy conversion and storage systems. Zinc-air batteries (ZABs) have excellent theoretical energy density (1086Wh kg -1 ), strong safety, and cost-effectiveness make them promising candidates. Therefore, exploring Zn-air batteries as next-generation energy conversion and storage solutions has significant research potential. However, the sluggish kinetics of ORR and OER in ZABs hinder their practical applications.
[0003] This problem is further exacerbated in flexible devices and extreme temperature conditions, which emphasizes the need for extensive research and development of electrocatalytic materials and modifications. The development and utilization of bifunctional electrocatalysts is crucial to solve the kinetic hysteresis problem in these reactions and thus promote the practical application of ZABs. However, the development of bifunctional electrocatalysts has reached a bottleneck period. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide an external field enhanced NiCo2S4@NiFe LDH / N-rGO heterostructure composite material and its application.
[0005] The technical solution adopted by the present invention is as follows: an external field enhanced NiCo2S4@NiFe LDH / N-rGO heterostructure composite material, the preparation process of which comprises the following steps:
[0006] (1) Preparation of NiCo2S4 hollow spheres;
[0007] (2) Synthesis of NiCo2S4@NiFe LDH: The iron source, nickel source and alkali were dissolved in water, and NiCo2S4 hollow spheres were added to synthesize NiCo2S4@NiFe LDH by a hydrothermal method;
[0008] Then NiCo2S4@NiFe LDH was combined with graphene to obtain NiCo2S4@NiFe LDH / N-rGO heterostructure composite material.
[0009] Preferably, in step (1), the preparation process of NiCo2S4 hollow spheres is as follows: CoSO4·7H2O is dispersed in a mixed solvent of EG and DMF, gradually heated to 130-160°C in an argon environment, then thiourea is slowly added, and the reaction is maintained under reflux conditions for 4-6 hours, Ni(OAc)2·4H2O is dispersed in a mixed solvent of EG and DMF, and then the mixture is added dropwise to the reaction solution and reacted at 160-180°C for 4-6 hours, and the dark precipitate obtained is collected by centrifugation, washed with deionized water and ethanol multiple times, and finally dried in a vacuum oven.
[0010] Preferably, the molar ratio of CoSO4·7H2O to Ni(OAc)2·4H2O is 2:1.
[0011] Preferably, in the mixed solvent of EG and DMF, the volume ratio of EG to DMF is 1:4.
[0012] Preferably, in step (2), the iron source is Fe(NO3)3·9H2O, the nickel source is Ni(NO3)2·6H2O, and the base is urea.
[0013] Preferably, in step (2), the reaction system is placed in an autoclave and placed in a continuous rolling oven for heating reaction, the reaction temperature is 110° C.-130° C., and the reaction time is 8-12 hours.
[0014] Preferably, in step (3), NiCo2S4@NiFe LDH, graphene dispersed in ethanol, NH3·H2O and ethanol are added to a reaction autoclave and reacted for 4-6 hours, and then subjected to three cycles of ultrasonic centrifugal washing to obtain the final product NiCo2S4@NiFe LDH / N-rGO.
[0015] The NiCo2S4@NiFe LDH / N-rGO heterostructure composite material as described above is used as an electrocatalytic material, and the electrocatalytic material is enhanced under photothermal conditions.
[0016] Application of the NiCo2S4@NiFe LDH / N-rGO heterostructure composite material for preparing electrodes as described above.
[0017] The external field enhanced NiCo2S4@NiFe LDH / N-rGO heterostructure composite material is used to prepare zinc-air batteries, wherein the zinc-air battery is a liquid zinc-air battery or a flexible zinc-air battery, and the zinc-air battery is photothermally enhanced.
[0018] A battery device comprises an electrode prepared from the NiCo2S4@NiFe LDH / N-rGO heterostructure composite material as described above, and also comprises a near-infrared light source, wherein the near-infrared light source irradiates the electrode prepared from the NiCo2S4@NiFe LDH / N-rGO heterostructure composite material.
[0019] In the present invention, NiCo2S4@NiFe LDH / N-rGO nanoparticles were successfully synthesized as catalysts, which showed excellent performance in ORR, OER electrochemical performance and battery performance in ZABs. The performance of electrocatalytic materials was further improved by using near-infrared light. Through the auxiliary effect of external field, the bifunctional performance of NiCo2S4@NiFe LDH / N-rGO nanoparticles was improved, and it showed more superior performance in liquid phase and flexible devices. The research of the present invention provides a powerful platform for further improving the performance and flexibility of ZABs by using photothermal effect, thus laying a foundation for future progress in its catalytic process and device development. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0021] Figure 1 Schematic diagram of the synthesis of external field enhanced NiCo2S4@NiFe LDH / N-rGO;
[0022] Figure 2 In the figure, (a) TEM image of NiCo2S4@NiFe LDH / N-rGO; (b) HRTEM image of NiCo2S4 and NiFe LDH, and the figure shows the corresponding enlarged HRTEM image;
[0023] Figure 3 (a) XRD pattern of NiCo2S4@NiFe LDH / N-rGO; (b) Raman spectrum of NiCo2S4@NiFe LDH / N-rGO; (cf) High-resolution XPS spectra of C1s, Fe 2p, Co 2p, and Ni 2p in NiCo2S4@NiFe LDH / N-rGO;
[0024] Figure 4(a) S2p and (b) N 1s in NiCo2S4@NiFe LDH / N-rGO; (c) full XPS spectrum of NiCo2S4@NiFe LDH / N-rGO composite material;
[0025] Figure 5 (a) ORR polarization curve, (b) CV of NiCo2S4@NiFe LDH / N-rGO in 0.1M KOH solution saturated with O2 and Ar, (c) methanol resistance test of NiCo2S4@NiFe LDH / N-rGO and Pt / C, (d) electron transfer number and H2O2 production of NiCo2S4@NiFe LDH / N-rGO in NiCo2S4@NiFe test, (e) Koutecky-Levich plot corresponding to different potentials, (f) RRDE measurement of the percentage of H2O2 of NiCo2S4@NiFe LDHN-rGO electrode at different potentials, (g) RRDE LSV polarization curve of NiCo2S4@NiFe LDH / N-rGO at 1600rpm in 0.1M KOH, (h) OER polarization curve, (i) Tafel slope curve;
[0026] Figure 6 (a) UV-visible absorption spectra of NiCo2S4@NiFe LDH / N-rGO, (b) NiCo2S4@NiFe LDH / N-rGO and Electrolyte at 1 mol L -1 Temperature changes of KOH and electrolyte over time. (c) NiCo2S4@NiFe LDH / N-rGO electrode at 1 mol L -1 The temperature in the KOH electrolyte changes with time;
[0027] Figure 7 Temperature changes of (a, b) NiCo2S4 / N-rGO and (c, d) NiFe LDH / N-rGO electrodes in electrolyte under 808 nm laser irradiation as a function of time (10 s, 50 s, 100 s, and 200 s);
[0028] Figure 8 (a) Polarization curves, (b) various electrodes at 1 mol L -1 10 mA cm for OER in KOH -2 The corresponding potentials under 10 mA cm-1, where NiCo2S4@NiFe LDH / N-rGO-Light represents the NiCo2S4@NiFe LDH / N-rGO electrode under light irradiation, (c) NiCo2S4@NiFe LDH / N-rGO at 10 mA cm-1-2 Stability test of the catalysts in OER with and without illumination, as well as RuO2, (d) polarization curves, (e) various electrodes at 0.1 mol L -1 The corresponding E of ORR in KOH 1 / 2 and J L , (f) NiCo2S4@NiFe LDH / N-rGO at a fixed potential of 0.6 V RHE Catalyst stability test with and without illumination, Pt / C without illumination;
[0029] Fig. 9 (a) CV curves of electrodes at different scan rates: NiCo2S4@NiFe LDH / N-rGO; (b) CV curves of electrodes at different scan rates under illumination: NiCo2S4@NiFe LDH / N-rGO; (c) The corresponding double-layer capacitance data obtained by CV measurement at different scan rates, (d) The corresponding double-layer capacitance data obtained by CV measurement at different scan rates under illumination, (e) The dual-functional curves of NiCo2S4@NiFe LDH / N-rGO and NiCo2S4@NiFe LDH / N-rGO catalysts under illumination and without illumination, (f) NiCo2S4@NiFe LDH / N-rGO, Pt / C+RuO2 and other reported 0.1 mol L -1 Comparative diagram of the bifunctional performance of potassium hydroxide bifunctional electrocatalysts;
[0030] Fig.10 (a) Schematic diagram of rechargeable ZAB, (b) open circuit voltage, (c) charge-discharge polarization curves, (d) power density polarization curves, (e) discharge curves of ZABs based on NiCo2S4@NiFe LDH / N-rGO and Pt / C+RuO2 at different current densities, (f) current density of 10 mA cm -2 The specific capacity of ZAB when
[0031] Fig.11 The current density of the zinc-air battery based on NiCo2S4@NiFe LDH / N-rGO air cathode under 5 min charging and 5 min discharging with and without light is (a) 10 mA cm -2 , (b) 25 mA cm -2 , (c) 50 mA cm -2 Long-term constant current charge and discharge curve when
[0032] Fig.12(a) Digital image of an LED powered by two series-connected battery cells based on NiCo2S4@NiFe LDH / N-rGO; (b) The assembled zinc-air battery can be used to power an LED light strip;
[0033] Fig.13 In the figure, the conductivity of PANa hydrogel at (a) 25 °C and (b) -40 °C.
[0034] Fig.14 (a) Photothermal-assisted FZABs scheme; (b) based on NiCo2S4@NiFe LDH / N-rGO and Pt / C+RuO2 at a current density of 1 mA cm -2 Specific capacity of FZABs under (c) discharge and power density diagram of batteries based on NiCo2S4@NiFe LDH / N-rGO and Pt / C+RuO2; (d) charge and discharge polarization curves of FZABs based on NiCo2S4@NiFe LDH / N-rGO and Pt / C+RuO2;
[0035] Fig.15 (a) Performance curves of NiCo2S4@NiFe LDH / N-rGO and Pt / C+RuO2 at 25°C (1 mA cm) -2 Cyclic current density; (b) NiCo2S4@NiFeLDH / N-rGO and Pt / C+RuO2 at 5 mA cm at 25 °C -2 Performance curves under cyclic current density; (c) NiCo2S4@NiFe LDH / N-rGO at 1 mA cm at 25 °C -2 Cyclic current density performance curves before and after illumination; (d) At 25°C, NiCo2S4@NiFe LDH / N-rGO at 5 mA cm -2 Cyclic current density performance curves before and after illumination; (e) at a current density of 2 mA cm -2 Cycling curves of NiCo2S4@NiFe LDH / N-rGO under various mechanical deformation conditions;
[0036] Fig.16 The discharge curves and power density diagrams of FZABs at different temperatures;
[0037] Fig.17 (a) Open circuit voltage of FZABs with NiCo2S4@NiFe LDH / N-rGO as air cathode before and after illumination at 25°C and -40°C; (b) Discharge and power density before and after illumination at 25°C and -40°C; (c) Current density of 1 mA cm based on NiCo2S4@NiFe LDH / N-rGO at 25°C and -40°C-2 Specific capacity of FZABs; (d) Discharge curves of NiCo2S4@NiFe LDH / N-rGO at different current densities before and after illumination at 25℃ and -40℃;
[0038] Fig.18 NiCo2S4@NiFe LDH / N-rGO 1mA cm -2 Cyclic current density performance curves before and after illumination at -40℃. DETAILED DESCRIPTION
[0039] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0040] In the following examples, the drugs and instruments used in the present invention are shown in Table 1 and Table 2.
[0041] Table 1 Main chemicals used
[0042]
[0043] Table 2 Main instruments used
[0044]
[0045] Embodiment 1:
[0046] Preparation of NiCo2S4@NiFe LDH / N-rGO, the synthesis route is as follows Figure 1 The specific steps are as follows:
[0047] (1) First, 2 mmol CoSO4·7H2O (0.562 g) was dissolved in 80 mL V EG (16mL) / V DMF NiCo2S4 hollow spheres (NiCo2S4 HSs) were synthesized in a 250mL three-necked flask containing a mixed solvent of 1:4 (64mL) by volume. The mixture was gradually heated to 145°C in an argon environment. Subsequently, a solution containing 10mmol of thiourea (0.7612g) was slowly added to the flask in 10mL of the mixed solvent, and the reflux condition was maintained for 5 hours. Subsequently, 10mL of a mixed solvent containing 1mmol of Ni(OAc)2·4H2O (0.6167g) was carefully dripped into the reaction solution and continued at 170°C for 5 hours.
[0048] (2) The dark precipitate was collected by centrifugation, washed with deionized water and ethanol several times, and finally dried in a vacuum oven at 60 °C for 12 h.
[0049] (3) NiCo2S4@NiFe LDH nanocomposite was synthesized by a single-step hydrothermal method. First, a solution containing 0.1346gFe(NO3)3·9H2O, 0.2g urea and 0.291g Ni(NO3)2·6H2O was dissolved in 34mL distilled water and magnetically stirred for 10 minutes. Subsequently, 0.219g NiCo2S4 hollow spheres were added to the solution and stirred continuously for 1 hour. The obtained solution was transferred to a 50mL reaction autoclave and kept at 120℃ in a continuous rolling oven for 10 hours. The solid product was washed with water and ethanol and then dried.
[0050] (4) The synthesized NiCo2S4@NiFe LDH was then combined with N-rGO. To this end, 16 mg of NiCo2S4@NiFeLDH, 8 mg of graphene (dissolved in 1.8 mg / mL ethanol), 1 mL of NH3·H2O, and 24 mL of ethanol were added to a reaction autoclave and allowed to react at 150 °C for 5 h. The resulting suspension was washed by ultrasonic centrifugation for three cycles to obtain the final product NiCo2S4@NiFe LDH / N-rGO.
[0051] The phase and morphology of NiCo2S4@NiFe LDH / N-rGO were characterized as follows:
[0052] (1) Transmission electron microscopy (TEM, HRTEM)
[0053] Take an appropriate amount of nanoparticle sample, disperse it in anhydrous ethanol, and evenly distribute it by ultrasound. Then, deposit the dispersion on a micro-grating support film, and observe the morphology under a transmission electron microscope (TEM) JEOL-2100F after drying.
[0054] (2) X-ray diffractometer (XRD)
[0055] The nanoparticle samples on the sample holder were compressed with cover glass and placed in the Bruker D 8 instrument, and their crystal structures were analyzed by scanning at different angles.
[0056] (3) Raman characterization
[0057] The ex situ Raman test was performed by pressing a small piece of nanoparticle powder sample flat on a silicon wafer using a Renishaw invia Raman spectrometer, with the excitation wavelength set to 532 nm and the objective lens set to 50×.
[0058] (4) X-ray photoelectron spectroscopy (XPS)
[0059] The chemical composition and valence state of the synthesized nanoparticle electrocatalysts were determined by X-ray photoelectron spectroscopy (XPS) under vacuum conditions.
[0060] (5) Ultraviolet UV
[0061] A certain amount of nanoparticle sample was dissolved in anhydrous ethanol and transferred into a cuvette (no more than 2 / 3 of the height) for subsequent analysis.
[0062] The test results are as follows:
[0063] The final target product NiCo2S4@NiFe LDH / N-rGO was obtained by solvothermal and hydrothermal methods. First, the overall morphology of the material was determined by transmission electron microscopy. Figure 2 The transmission electron microscope image of NiCo2S4@NiFe LDH / N-rGO in a shows clear cactus-shaped hollow spheres with uniform size and diameter of about 1.2μm, which are composed of a large number of interconnected nanowires and nanosheets. The diameter of these nanowires is about 15nm to 25nm, and they extend outward to form specific nanosheets and surfaces close to NiCo2S4. The overall NiCo2S4@NiFeLDH is attached to the graphene substrate. Figure 2 b provides insights into the different sizes of the different components of the heterostructure. Further observation by high-resolution transmission electron microscopy (HRTEM) revealed that the interplanar spacing of NiCo2S4 in the NiCo2S4@NiFe LDH / N-rGO heterostructure is 0.232nm, which corresponds to the (311) crystal plane of NiCo2S4. The interplanar spacing of NiFe LDH is 0.246nm, which is the (101) crystal plane.
[0064] The synthesis of NiCo2S4@NiFe LDH / N-rGO was verified by X-ray diffraction (XRD) and detailed structural information was provided. The XRD pattern showed that the nanocomposite catalyst was composed of NiCo2S4 (JCPDS No. 20-0782) and NiFe LDH (JCPDS No. 40-0215), such as Figure 3 The peaks at 26.8°, 31.6°, 50.5° and 55.3° correspond to the (220), (311), (511) and (440) planes of NiCo2S4, respectively, and the remaining peaks are attributed to NiFe LDH
[16] .also, Figure 3 b shows the vibration signal in the Raman spectrum. The Ni-O vibration peak of NiCo2S4@NiFe LDH / N-rGO is at 476 cm -1 ,Co-O vibration signal at 550cm -1 , the Fe-O signal peak is at 671cm -1, confirming the Ni-O, Co-O, and Fe-O vibrations in the NiCo2S4@NiFe LDH / N-rGO material. The chemical state of the samples was studied using X-ray photoelectron spectroscopy (XPS). The C 1s spectrum showed the presence of C=C with a binding energy of 284.4-284.5 eV. The higher binding energy peaks observed in all samples were attributed to carbon oxides such as O=C or OC=O ( Figure 3 c). In NiCo2S4@NiFe LDH, the Fe 2p XPS peaks are 724.5eV and 715.9eV, corresponding to Fe2p 1 / 2 and Fe 2p 3 / 2 Signal Fe 3+ state, and the other peak is at 711.7 eV, corresponding to Fe 2p 3 / 2 Signal Fe 2+ state( Figure 3 d). The Co2p XPS spectrum has four peaks at 780.4 / 795.9eV and 782.2 / 797.6eV, representing Co 3+ State and Co 2+ state( Figure 3 e). The Ni 2p XPS spectrum of NiCo2S4@NiFe LDH has two obvious peaks at 855.5eV and 873.1eV, corresponding to Ni2p 3 / 2 and Ni 2p 1 / 2 Ni 2+ state( Figure 3 f), In addition, the presence of higher binding energy satellite peaks indicates the presence of Ni 3+ state, Ni2p 3 / 2 and Ni 2p 1 / 2 The binding energies of the orbitals are 857.6 eV and 879.0 eV, respectively. These results provide strong evidence for the successful synthesis of NiCo2S4@NiFe LDH / N-rGO.
[0065] For the S2p spectrum of NiCo2S4@NiFe LDH / N-rGO, the peaks at 163.0 eV and 161.6 eV are S 2- , the peak at 168.0 eV comes from sulfate ( Figure 4 a). The high-resolution N1s spectrum can be further divided into three peaks centered at 397.78 eV (pyridinic N), 398.91 eV (pyrrolic N), and 399.79 eV (graphitic N). Studies have shown that pyridinic nitrogen and graphitic nitrogen have good electron-accepting abilities, which can promote the adsorption of oxygen and thus reduce the overpotential of ORR. Pyridinic N and pyrrolic N can serve as metal coordination ( Figure 4 b). Figure 4c The presence of Ni, Co, Fe, S, O, and N in the NiCo2S4@NiFe LDH / N-rGO composite was confirmed, confirming the successful synthesis of the NiCo2S4@NiFe LDH heterostructure.
[0066] Embodiment 2:
[0067] The preparation of NiCo2S4@NiFe LDH / N-rGO working electrode includes the following steps:
[0068] (1) Pretreatment of glassy carbon electrode:
[0069] Before polishing, wipe the electrode surface clean in advance, then add aluminum oxide polishing powder to 1μm, 0.3μm and 0.05μm deerskin sandpaper respectively, and add a small amount of deionized water. Then start polishing the electrode with sandpaper for about three minutes, and the polishing path is an "8" shape or a circle in one direction. After every 3 minutes of polishing, the electrode needs to be ultrasonically cleaned in a mixed solution of anhydrous ethanol and ultrapure water (at a ratio of 1:1) for about 15 seconds, and then blown dry with nitrogen.
[0070] (2) Preparation of working electrode:
[0071] First, weigh 8 mg of catalyst sample and 3 mg of Ketjen black into a 5 mL centrifuge tube, then add 1 mL of anhydrous ethanol to the centrifuge tube, and then add 40 μL of 5% Nafion solution to the centrifuge tube, and put it into an ultrasonic machine for 40 min-60 min, shaking the centrifuge tube while ultrasonicating for easy dispersion. After waiting for the end of the ultrasound, use a pipette to draw 20 μL of catalyst ink and evenly drop it on the polished glassy carbon electrode surface. Before conducting relevant electrocatalytic performance tests, it needs to be dried naturally or placed in a 60°C oven to complete drying.
[0072] In addition, a commercial working electrode of 20 wt % Pt / C and RuO2 catalyst was prepared using the same method as a comparative example.
[0073] Embodiment 3:
[0074] The electrochemical performance of the NiCo2S4@NiFe LDH / N-rGO working electrode prepared in Example 2 and the working electrode of commercial 20wt% Pt / C and RuO2 catalysts were tested. The test process is as follows:
[0075] The electrochemical performance of OER and ORR was tested using a conventional three-electrode system. In this device, the geometric area is 0.196 cm -2The catalyst-loaded rotating disk electrode (RDE) was used as the working electrode and the carbon rod was used as the counter electrode. The ORR measurement used an Ag / AgCl electrode under saturated KCl conditions as the reference electrode, while the OER measurement used a 1 mol L -1 Hg / HgO electrode under KOH conditions. ORR test was performed by linear sweep voltammetry (LSV) at 0.1 mol L -1 The scan rate in KOH solution was 5 mV s -1 , while the OER test was performed at 1 mol L -1 90% iR compensation was used in KOH solution. The slope of the obtained curve was calculated according to the Tafel equation η = blog (j / j0).
[0076] Electrochemical impedance spectroscopy (EIS) analysis was performed in the frequency range of 0.01 to 100 K, and the determination of the effective catalyst surface area (ECSA) relied on the measurement of the double layer capacitance (Cdl). The catalyst stability was evaluated by it test, and the potential calibration was performed using the Nernst equation E at the reversible hydrogen electrode (RHE). RHE =E Ag / AgCl +0.0591×pH+0.197,E RHE =E Hg / HgO +0.0591×pH+0.098-iR. RRDE measurement uses equations (1) and (2) to calculate the percentage of H2O2 and the number of transferred electrons (n):
[0077]
[0078] The current collection efficiency N of the Pt ring was determined to be 0.40 by reducing K3Fe[CN]6, where I d is the disk current, I r is the ring current.
[0079] In order to calculate the number of transferred electrons, the present invention tests the LSV curves at different speeds, and the number of transferred electrons n can be calculated by the following KL equation.
[0080]
[0081] B=0.62nFC0D0 2 / 3 ν -1 / 6 Formula (4)
[0082] Equations (3) and (4) represent the measured current density (j) and kinetic density (j) respectively. K ) and limiting current density (j L ). The angular velocity of RDE is represented by ω, the number of transferred electrons is represented by n, and the Faraday constant F = 96485C mol -1C0 represents the volume concentration of O2 in the electrolyte (1.2×10 -3 mol L -1 ), D0 represents the diffusion coefficient of O2 in the electrolyte (1.2×10 -3 mol L -1 ),υ represents the kinematic viscosity of the electrolyte 0.01cm 2 s -1 .
[0083] The electrochemical performance of the material was tested by carrying out bifunctional performance tests on the obtained NiCo2S4@NiFe LDH / N-rGO electrocatalyst. These tests were carried out in an oxygen-saturated potassium hydroxide electrolyte using a three-electrode system with all potentials calibrated to the reversible hydrogen electrode (RHE) as a reference. The performance of the electrocatalyst was compared with that of a noble metal-based Pt / C+RuO2 benchmark catalyst.
[0084] At 0.1 mol L -1 The ORR performance was evaluated in saturated potassium hydroxide aqueous solution. Figure 5 In a, the heterostructure NiCo2S4@NiFe LDH / N-rGO has excellent ORR activity with an onset potential of 0.90 V and a half-slope potential (E 1 / 2 ) is 0.809V, which is better than NiCo2S4 HSs / N-rGO (E 1 / 2 =0.763V), FeNi LDH NWs / N-rGO(E 1 / 2 =0.695V), close to the commercial Pt / C catalyst (E 1 / 2 =0.834V). The incorporation of the hollow structure consisting of NiFe LDH and NiCo2S4 plays an important role in promoting the ORR activity of the material, thereby greatly improving the ORR performance of NiCo2S4@NiFe LDH. This enhancement is attributed to the optimization of the electronic structure of the non-uniform interface after the addition of NiFe LDH to NiCo2S4. This optimization promotes the adsorption / desorption of intermediates during the ORR process, thereby improving the catalytic performance overall. Figure 5 The cyclic voltammetry (CV) curves shown in b clearly show a distinct cathodic peak at 0.702 V in the presence of O2 compared to that in the presence of N2. This observation strongly suggests that the reduction of NiCo2S4@NiFe LDH / N-rGO is mainly attributed to the catalytic effect of this material on O2. The methanol tolerance of NiCo2S4@NiFe LDH / N-rGO was evaluated, as shown in Figure 5. Figure 5 c shows that even if methanol (3 mol L -1), the current density of NiCo2S4@NiFe LDH / N-rGO is also basically unaffected, while the current density of Pt / C is significantly reduced. This emphasizes that the NiCo2S4@NiFe LDH / N-rGO material has excellent methanol resistance, which exceeds the performance of Pt / C. In order to clarify the kinetics of ORR, the present invention performed Koutecky-Levich analysis. The calculated number of transferred electrons of NiCo2S4@NiFe LDH / N-rGO is about 4.0 ( Figure 5 d. Figure 5 e). This is in good agreement with the value of about 3.98 obtained by rotating ring disk electrode (RRDE) measurements ( Figure 5 f. Figure 5 g). In addition, it is worth noting that the yield of the catalytic product hydrogen peroxide is less than 1% ( Figure 5 f), which may be due to the direct generation of hydroxide ions and water during the oxygen reduction process of NiCo2S4@NiFe LDH / N-rGO. These results collectively indicate that there is a significant synergistic effect between NiCo2S4 and NiFe LDH, which, together with the well-defined nanostructure of NiCo2S4@NiFe LDH / N-rGO, ultimately improves the ORR activity.
[0085] In a standard linear sweep voltammetry (LSV) experiment, the present invention measured the -2 (E j=10 ) to evaluate and compare the OER activities of the synthesized catalysts and benchmark noble metal catalysts. Figure 5 The LSV curve shown in h shows that NiCo2S4@NiFe LDH / N-rGO(E j=10 =311mV), FeNi LDH / N-rGO(E j=10 =320mV), even higher than the widely used RuO2 (E j=10 =312mV). In addition, Figure 5 In i, the Tafel slope of NiCo2S4@NiFe LDH / N-rGO (99.9 mV / decade) is in sharp contrast to that of RuO2 (154 mV / decade). NiCo2S4@NiFeLDH / N-rGO has excellent OER properties, which can be attributed to its inherent high catalytic activity and unique layered hollow heterostructure. The incorporation of NiFe LDH into NiCo2S4 optimizes the electronic structure of the heterogeneous interface and enhances the adsorption / desorption of intermediates during the OER process, thereby improving the catalytic performance.
[0086] Embodiment 4:
[0087] The photothermal effect cell performance was tested on the NiCo2S4@NiFe LDH / N-rGO working electrode prepared in Example 2 and the commercial working electrode with 20wt% Pt / C and RuO2 catalyst.
[0088] In order to study the photothermal assisted performance of the supported catalyst, the electrode was heated to 0.1 mol L -1 or 1 mol L -1 The KOH solution was irradiated with 808 nm laser (MDL-H-808-5W) in an electrolytic cell. The electrode temperature was monitored using an infrared thermal imager (FLIR E50) and the temperature-time curve was recorded until a stable temperature was reached. The irradiation power could be varied between 0 and 5.0 W cm -2 The laser irradiation was carried out for 2 minutes before each test, and then the corresponding electrochemical test was carried out.
[0089] In order to prove that the photothermal effect promotes the activity of electrocatalytic reaction, the external field response photothermal effect of NiCo2S4@NiFe LDH / N-rGO was systematically investigated. Based on the UV-VIS spectrum of NiCo2S4@NiFe LDH / N-rGO solution ( Figure 6 a), strong absorption was observed at 700-850 nm, indicating that NiCo2S4@NiFe LDH / N-rGO may convert light into heat under near-infrared (NIR) illumination. The photothermal effect of the material was studied by irradiating 1.0 mol L -1 KOH solution attached to the NiCo2S4@NiFe LDH / N-GO nanomaterial electrode. Figure 6 b. Figure 6 c found that the electrode temperature rose rapidly, reaching 56.7°C within 20s of illumination, and reached 83°C and stabilized at 65s. In sharp contrast, the electrolyte temperature remained almost unchanged. NiCo2S4@NiFe LDH / N-GO nanomaterials can effectively convert 808nm laser energy into heat, proving that the heating of the electrode by near-infrared light is local. These studies provide strong conditions for improving ORR and OER performance. It is worth noting that the final equilibrium temperature of the NiCo2S4@NiFe LDH / N-rGO electrode (87.0°C) is much higher than that of the NiCo2S4 (46.8°C) and FeNi LDH / N-rGO (53.5°C) electrodes ( Figure 7ad). This proves that the electrocatalyst formed by the composite of NiCo2S4 and FeNiLDH / N-rGO has a more excellent photothermal response. These results together reflect the ultra-sensitive photothermal response of the NiCo2S4@NiFe LDH / N-rGO catalyst, paving the way for further improving its electrocatalytic performance by utilizing its profound photothermal effect.
[0090] To evaluate the enhancement of the catalytic activity by the photothermal effect, the OER / ORR performances of the catalysts with and without 808 nm NIR irradiation were systematically evaluated by linear sweep voltammetry (LSV). Figure 8 The LSV curves of OER shown in a, b indicate that the potential of the NiCo2S4@NiFe LDH / N-rGO electrode is significantly reduced from 1.492 V to 1.456 V upon exposure to NIR irradiation. Figure 8 In c, NiCo2S4@NiFe LDH / N-rGO exhibits significantly more stable performance, with the current density decreasing by only 12.7% after maintaining a stable potential for 10 hours, in sharp contrast to the commercial RuO2 catalyst (23.7%). At the same time, NiCo2S4@NiFe LDH / N-rGO has excellent bifunctional activity, with NiCo2S4 and N-rGO providing excellent active sites for the ORR reaction. The effect of the photothermal effect on the performance of the ORR was evaluated in a 0.1M saturated potassium hydroxide aqueous solution. Figure 8 d. Figure 8 e, the heterostructure NiCo2S4@NiFe LDH / N-rGO has excellent ORR activity with an onset potential of 0.90 V and a half-wave potential (E 1 / 2 ) is 0.809V. Under light conditions, the half-wave potential (E 1 / 2 ) is further increased to 0.82V. Figure 8 In Figure f, the current density of NiCo2S4@NiFe LDH / N-rGO shows remarkable stability, and after 10 hours of ORR process, it only decreases by 6.8% compared with the initial value, which is in sharp contrast to the commercial ORR catalyst (the latter decreases significantly by 27.5%). This phenomenon can be attributed to the fact that the external NiFe LDH can serve as a protective layer for the internal NiCo2S4, thereby reducing its corrosion and ensuring continuous electrochemical activity stability. Under the photothermal effect, the current density of the material shows even better stability, and after 10 hours, it only decreases by 6.12% compared with the initial value, which proves that NiCo2S4@NiFe LDH / N-rGO has superior ORR performance with the help of the photothermal effect.
[0091] Theoretically, the improvement of catalytic activity is usually associated with a large exposed electrochemically active surface area (ECSA), which can therefore be evaluated based on the double-layer capacitance (Cdl) of the sample. Fig. 9 ad shows that the Cdl of NiCo2S4@NiFe LDH / N-rGO is 10 mF cm -2 Under near-infrared illumination, the Cdl further increases to 15 mF cm -2 . This can be attributed to the fact that the temperature increase on the surface of the NiCo2S4@NiFe LDH / N-rGO electrode promotes the activation and effective collision of reactive species, resulting in more active sites being accessible to the electrolyte. Therefore, NiCo2S4@NiFe LDH / N-rGO has excellent photothermal conversion performance, which can enhance the electrocatalytic process of ORR / OER. As a catalyst with bifunctional properties, NiCo2S4@NiFe LDH / N-rGO provides an excellent potential difference of 0.683V (ΔE=E j=10 -E 1 / 2 ) value, which is further reduced to only 0.636V ( Fig. 9 e), indicating that this bifunctional electrocatalyst has excellent reversible catalytic activity and outstanding stability. This achievement makes it one of the most promising catalysts among the recently reported noble metal-free bifunctional electrocatalysts, such as Fig. 9 f.
[0092] Embodiment 5:
[0093] The rechargeable ZABs battery performance test was carried out on the NiCo2S4@NiFe LDH / N-rGO working electrode prepared in Example 2 and the commercial working electrode with 20wt% Pt / C and RuO2 catalyst.
[0094] The zinc-air battery was tested using a CHI 760e electrochemical workstation. The polished zinc sheet was used as the anode and the carbon paper loaded with NiCo2S4@NiFe LDH / N-rGO was used as the cathode. The electrolyte consisted of 6 mol L -1 KOH and 0.2 mol L -1 Zn(CH3COO)2. For the illumination test, a small rectangular aperture of 0.5 cm*0.8 cm was engraved on the zinc sheet, and the zinc sheet was directly exposed to the illuminated air cathode when the near-infrared lamp was turned on. For the photothermal-assisted ZABs test, near-infrared light was used for 2 minutes to achieve temperature equilibrium before evaluating the battery performance. All measurements were performed at room temperature, and the catalyst loading on the air electrode was 1.0 mg cm -2 .
[0095] Given the impressive bifunctional activity and stability observed, the present inventors proceeded to assemble rechargeable ZABs to evaluate their feasibility for practical applications. These Zn sheets were prepared using Zn sheets as anodes and NiCo2S4@NiFe LDH / N-rGO catalysts as air cathodes, as Fig.10 As shown in a. Fig.10 b It can be seen that under NIR conditions, an open circuit voltage (OCV) of 1.49 V was achieved and remained stable for 10 hours, significantly exceeding the 1.439 V of ZABs based on Pt / C and RuO2. In addition, over the entire current density range, NiCo2S4@NiFe LDH / N-rGO-ZABs exhibited a narrower charge / discharge voltage gap than Pt / C-RuO2-ZABs ( Fig.10 c). Under NIR light irradiation, the charge-discharge voltage gap is further reduced. Fig.10 The polarization curve in d shows that the ZABs using NiCo2S4@NiFe LDH / N-rGO achieve an impressive power of 188 mW cm -2 , exceeding Pt / C+RuO2 (95.1mW cm -2 ). It is noteworthy that the presence of light leads to a significant enhancement in the maximum power density, reaching 206 mW cm -2 To evaluate the discharge rate capability, the present invention monitors the discharge voltage over a range of current densities. Fig.10 As shown in e, the control current is 1~20mA cm -2 The assembled battery maintains stable discharge. The results show that NiFe LDH / N-rGO, as the air cathode, exhibits a better discharge platform than Pt / C-RuO2. In addition, with the help of the photothermal effect, the discharge rate stability of NiCo2S4@NiFe LDH / N-rGO is further enhanced. Fig.10 The experimental results show that the specific discharge capacity of ZAB based on NiCo2S4@NiFe LDH / N-rGO reaches 732 mA h g under no light conditions. -1 , exceeding Pt / C-RuO2 (703mA hg -1 ). In addition, the present invention observed that exposure to NIR light further improved the discharge capacity to 783 mA hg -1 .
[0096] The long-term charge-discharge cycling of ZABs was evaluated. Fig.11 At a current density of 10 mA cm -2 The following lasted for 4010 cycles ( Fig.11a). The introduction of the photothermal effect further improves the cell performance, enabling it to reach 7437 cycles while maintaining an impressive round-trip efficiency of 51.25%. This exceptional stability can be attributed to the local heating of the cathode surface, which prevents potential electrolyte volatilization, leakage, and loss of anode Faradaic efficiency. When the current density is increased to 25 mA cm -2 When NiCo2S4@NiFe LDH / N-rGO was used, it showed consistent charge / discharge voltage behavior and round-trip efficiency ( Fig.11 b). Subsequently, in cycling tests under NIR illumination, the NiCo2S4@NiFe LDH / N-rGO-based ZABs showed remarkable stability over 8285 cycles at high current density while maintaining a good initial round-trip efficiency of 51.48%. This emphasizes that the photothermal effect of the material at high current density further enhances the rechargeable cycling stability performance. Fig.11 In c, the current level increases to a higher 50 mA cm -2 When exposed to NIR illumination, the ZABs still exhibited remarkable stability, maintaining the cycling performance for approximately 255 cycles. Notably, under such conditions, the performance of ZABs tends to generally decline, mainly attributed to the accelerated corrosion of zinc and the simultaneous deterioration of the electrolyte. Meanwhile, when exposed to NIR illumination, the number of stable cycles increased significantly to 340 cycles. This observation highlights the ability of the photothermal effect to improve the charge-discharge cycling stability of ZABs under high current density conditions.
[0097] In addition, the assembled ZABs can effectively power small light bulbs and LED light strips ( Fig.12 a. Fig.12 b). These applications highlight its excellent charge-discharge performance, consistent with the stability observed in ORR and OER tests.
[0098] Embodiment 6:
[0099] The NiCo2S4@NiFe LDH / N-rGO working electrode prepared in Example 2 and the commercial working electrode with 20 wt% Pt / C and RuO2 catalyst were assembled and the performance of the rechargeable flexible zinc-air battery was tested.
[0100] Using a CHI 760e electrochemical workstation, a polished zinc sheet was used as the anode, and the NiCo2S4@NiFe LDH / N-rGO catalyst was introduced into a fluid collector composed of carbon cloth and nickel foam as the air cathode. PANa hydrogel was used as the solid electrolyte for all rechargeable FZABs, which consisted of an air cathode and a zinc anode, and the two sides of the hydrogel layer were fixed by a breathable and waterproof tape. The FZABs were tested in a low-temperature stirring reaction bath (DHJF-4002) with a temperature range of -10℃ to 25℃, similar to the procedure used for the performance testing of rechargeable liquid zinc-air batteries. To prepare PANa hydrogel, sodium hydroxide solution (5mL, 4g) was added to an aqueous solution of acrylic acid (AA) monomer (7.2mL AA in 10ml H2O) and stirred at 0℃; AA monomer was prepared by vacuum distillation. Using ammonium persulfate (APS, 0.11 g) as an initiator, a chemical crosslinker N,N'-methylenebisacrylamide (MBAA) was added to the neutralization solution, stirred at 0°C for half an hour, and then O2 was removed with N2 gas; free radical polymerization was carried out at 75°C for 2 hours, completely dried at 50°C, and immersed in a mixture of KOH and Zn(Ac)2 for 12 hours; finally, the filter paper was dried to prepare a polymer hydrogel as a rechargeable FZABs electrolyte for experimental use.
[0101] In order to cope with the growing demand for flexible electronic devices, the present invention successfully fabricated a flexible device of FZABs. Rechargeable FZABs ( Fig.14 a) The present invention evaluates the tolerance of the hydrogel by conducting tests at room temperature and low temperature, demonstrating its potential for practical application in FZABs. Fig.13 a. Fig.13 As shown in Figure 2, PANa hydrogel has good electrical conductivity at 25°C, measured as 273.79 mS / cm. Impressively, it maintains a high conductivity of 72.07 mS / cm even at extremely low temperatures (-40°C). Hydrogels with excellent electrical conductivity are an important prerequisite for the preparation of high-performance flexible zinc-air batteries.
[0102] Fig.14 bd is a comparison of the power density, charge-discharge polarization curves, and specific capacity of NiCo2S4@NiFe LDH / N-rGO and Pt / C-RuO2 as air cathodes of FZABs. At room temperature, the peak power density reaches 111 mW cm -2 , which is higher than 53.18 mW cm of Pt / C-RuO2 -2 and advanced FZABs (typically <50 mW cm -2 )( Fig.14 b). In addition, the FZABs using NiCo2S4@NiFe LDH / N-rGO showed a significantly reduced charge voltage and a narrower charge / discharge voltage gap compared to Pt / C-RuO2 ( Fig.14 c). Meanwhile, the FZABs battery based on NiCo2S4@NiFe LDH / N-rGO showed a stronger discharge capacity with a specific capacity of 761.04 mA h g -1 , exceeding the 696.15 mA hg of Pt / C-RuO2 -1 Specific capacity( Fig.14 d).
[0103] In order to demonstrate the excellent battery performance of NiCo2S4@NiFe LDH / N-rGO applied to FZABs, it was compared with Pt / C-RuO2. At room temperature (25 °C), the current density was 1 mA cm -2 When the NiCo2S4@NiFe LDH / N-rGO-FZABs were charged at 1.9645V and 1.2305V, the round-trip efficiency was 62.64%. Even after 1300 cycles, the battery maintained a high round-trip efficiency of 51.72%, with a slight increase of 168mV in the charge and discharge voltage. In contrast, the voltage gap of Pt / C-RuO2-FZABs widened significantly after 516 cycles ( Fig.15 a). At high current density (5 mA cm -2 ), the NiCo2S4@NiFe LDH / N-rGO-FZABs battery successfully underwent 807 charge-discharge cycles. However, the control experiment using Pt / C-RuO2-FZABs showed that as the voltage gap increased, only 113 stable charge-discharge cycles ( Fig.15 b) To explore the influence of photothermal effect on material performance in battery applications, Fig.15 c. Fig.15 d Experiment. At a current density of 1 mA cm -2 When NIR illumination was applied, the results showed that after 1300 cycles, the initial round-trip efficiency was 57.43% ( Fig.15 c). At high current density (5 mA cm -2 ) under the condition of irradiation, the NiCo2S4@NiFe LDH / N-rGO-FZABs battery successfully underwent 807 charge and discharge cycles. The round-trip efficiency before and after illumination increased from 52.4% to 67.4% ( Fig.15 d). More practically, the zinc-air battery exhibited stable charge and discharge voltage under constant current conditions after various deformation and failure cycles (such as bending, twisting, folding, and recovery), confirming its excellent flexibility ( Fig.15 e).
[0104] The NiCo2S4@NiFe LDH / N-rGO-FZABs battery maintains a stable open circuit voltage of about 1.44 V at room temperature ( Fig.17 a), maintained at 1.327V at extremely low temperatures (-40°C). In order to verify the enhancement effect of photothermal effects on FZABs, the present invention added a NIR source. The results showed that the open circuit voltage can reach 1.489V at room temperature and 1.363V at extremely low temperatures (-40°C). This shows that under light irradiation, the heat generated by photothermal heating not only offsets the adverse effects of the low temperature environment, but also improves the catalytic activity. The power density of flexible zinc-air batteries at different temperatures is shown in Figure 2. Fig.16 At room temperature, the peak power density reaches 111 mW cm -2 The power density decreases with decreasing temperature. At -10℃, -20℃, -30℃ and -40℃, the power density is 93.15mW cm -2 、74.5mW cm -2 、58.16mW cm -2 and 46.47 mW cm -2 Under light, the FZABs based on NiCo2S4@NiFe LDH / N-rGO can reach 151.7 mW cm at 25 °C. -2 The power density can reach 49.95mW cm at -40℃ -2 The power density ( Fig.17 b).
[0105] Compared with the condition without NIR light, the FZABs based on NiCo2S4@NiFe LDH / N-rGO exhibited superior discharge capability under NIR light with a specific capacity of 780.95 mA h g -1 (25℃) and 738.23mA hg -1 (-40℃)( Fig.17 c). Fig.17 d shows the control current (0.1 mA cm -2 to 2mA cm -2 ), the assembled battery showed stable discharge characteristics. As the current decreased, the voltage platform was restored, indicating that NiCo2S4@NiFe LDH / N-rGO had good discharge rate performance as an air cathode. Under light conditions, the discharge voltage increased from 1.369V to 1.381V (0.1mA cm -2 Increase to 2mAcm -2), while at -40 °C the discharge voltage increased from 1.260 V to 1.320 V, confirming that light irradiation increased the voltage at both temperatures.
[0106] FZABs have excellent long-term stability at low temperatures. At -40°C, the battery cycled 1300 times with an initial round-trip efficiency of 46.8%, and cycled up to 3480 cycles under NIR illumination with an initial round-trip efficiency of 58.9%, proving that illumination improves the charge-discharge cycle stability of FZABs ( Fig.18 ).
[0107] In summary, NiCo2S4@NiFe LDH / N-rGO was successfully synthesized and applied in ZABs and FZABs, showing excellent performance. The remarkable photothermal effect enables immediate and local heating of the working electrode, surpassing the traditional heating strategy without the need for additional energy input. Under photothermal stimulation, ΔE increased to 0.636 V, exceeding most of the previously reported non-precious metal-based catalysts. The resulting photothermal-assisted ZABs achieved power densities of 206 mW cm at 25 °C, respectively. -2 and 151 mW cm -2 The long-term cycling stability of the liquid phase device is 8285 cycles, and the long-term cycling stability of the solid-state device is 1300 cycles. Under the photothermal effect, FZABs show excellent power density at sub-zero temperature (49.95 mW cm at -40 °C). -2 ), excellent charge-discharge cycling (3480 cycles at -40°C), and excellent mechanical flexibility. The present study provides a powerful platform for further improving the performance and flexibility of ZABs, thereby laying the foundation for future advances in catalytic processes and device development.
[0108] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. An external field enhanced NiCo2S4@NiFe LDH / N-rGO heterostructure composite material, characterized in that: The preparation process includes the following steps: (1) Preparation of NiCo2S4 hollow spheres; (2) Synthesis of NiCo2S4@NiFe LDH: The iron source, nickel source and alkali were dissolved in water, and NiCo2S4 hollow spheres were added to synthesize NiCo2S4@NiFe LDH by a hydrothermal method; Then NiCo2S4@NiFe LDH was combined with graphene to obtain the external field enhanced NiCo2S4@NiFe LDH / N-rGO heterostructure composite material.
2. The NiCo2S4@NiFe LDH / N-rGO heterostructure composite material according to claim 1, characterized in that: In step (1), the preparation process of NiCo2S4 hollow spheres is as follows: CoSO4·7H2O is dispersed in a mixed solvent of EG and DMF, gradually heated to 130-160°C in an argon environment, then thiourea is slowly added, and the reaction is maintained under reflux conditions for 4-6 hours, Ni(OAc)2·4H2O is dispersed in a mixed solvent of EG and DMF, and then the mixture is added dropwise to the reaction solution and reacted at 160-180°C for 4-6 hours, and the obtained dark precipitate is collected by centrifugation, washed with deionized water and ethanol multiple times, and finally dried in a vacuum oven.
3. The NiCo2S4@NiFe LDH / N-rGO heterostructure composite material according to claim 1, characterized in that: The molar ratio of CoSO4·7H2O and Ni(OAc)2·4H2O is 2:1; In the mixed solvent of EG and DMF, the volume ratio of EG to DMF is 1:
4.
4. The NiCo2S4@NiFe LDH / N-rGO heterostructure composite material according to claim 1, characterized in that: In step (2), the iron source is Fe(NO3)3·9H2O, the nickel source is Ni(NO3)2·6H2O, and the alkali is urea.
5. The NiCo2S4@NiFe LDH / N-rGO heterostructure composite material according to claim 4, characterized in that: In step (2), the reaction system is placed in an autoclave and placed in a continuous rolling oven for heating reaction at a reaction temperature of 110° C.-130° C. and a reaction time of 8-12 hours.
6. The NiCo2S4@NiFe LDH / N-rGO heterostructure composite material according to claim 1, characterized in that: In step (3), NiCo2S4@NiFe LDH, graphene dispersed in ethanol, NH3·H2O and ethanol are added into a reaction autoclave and reacted for 4-6 hours, and then washed by ultrasonic centrifugation for three cycles to obtain the final product NiCo2S4@NiFe LDH / N-rGO.
7. Use of the NiCo2S4@NiFe LDH / N-rGO heterostructure composite material as described in any one of claims 1 to 6 as an electrocatalytic material, wherein the electrocatalytic material is enhanced under photothermal conditions.
8. Use of the NiCo2S4@NiFe LDH / N-rGO heterostructure composite material as described in any one of claims 1 to 6 to prepare electrodes.
9. Use of the NiCo2S4@NiFe LDH / N-rGO heterostructure composite material as described in any one of claims 1 to 6 to prepare a zinc-air battery, wherein the zinc-air battery is a liquid zinc-air battery or a flexible zinc-air battery, and the zinc-air battery is enhanced under the irradiation of a near-infrared light source.
10. A battery device, comprising an electrode prepared from the NiCo2S4@NiFe LDH / N-rGO heterostructure composite material according to any one of claims 1 to 6, characterized in that: It also includes a near-infrared light source, which irradiates the electrode prepared by the NiCo2S4@NiFe LDH / N-rGO heterogeneous structure composite material.
Citation Information
Patent Citations
Preparation method of ultra-fast nickel-iron layered double hydroxide / graphene nanocluster heterojunction catalyst
CN115360366A
Preparation method of NiCo2S4-coated NiCo-LDH / NF electrode material for photo-assisted supercapacitor
CN117393334A
Electrode catalyst composite containing 2d transition metal chalcogenide material for water electrolysis and manufacturing method thereof
US20240200211A1